Hypomania/Mania Induced by Cessation of Antidepressant Drugs - (:unkn) unknown (TURKIYE SINIR VE RUH SAGLIGI DERNEGI, 2008)
Although rarely reported, the induction of hypomanic/manic episodes due to sudden or gradual cessation of antidepressant drugs is a phenomenon observed in clinical settings. Herein we present 2 patients that hod manic episodes induced by gradual cessation of antidepressant drugs. Common features of both cases were as follows: patients were female; a major depressive episode was the reason for starting treatment; familial loading for unipolar depressive disorder; venlafaxine was administered for treatment of the episode, mood elevation symptoms while gradually decreasing the medication dose; absence of physical symptoms related to withdrawal; antipsychotic and mood stabilizing drugs were required for the treatment of the episode. In both cases 1) a hypomanic/manic episode induced by the use of antidepressants, 2) agitated depression, 3) physical withdrawal syndrome, and 4) spontaneous episodes in the natural course of the illness were the 4 different states that were taken into consideration for differential diagnosis. Hypomanic/manic episodes induced by cessation of antidepressant drugs are thought to shed light on the etiology of bipolar disorder which this report discusses with reference to the case reports.
Keywords: antidepressive drug; mania; hypomania; cessation; INDUCED MANIA; WITHDRAWAL; DISCONTINUATION